VERBS EXPRESSING THE MEANING OF "IRREGULAR REPETITION" - Sahakyan David Arsenovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article presents the "irregular repetition" of the verb. The issue of "irregular repetition" is considered as the meaning conveyed by derivative verbs formed in the affix way: to enter, walk,etc.